2020
DOI: 10.1175/wcas-d-19-0122.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Constraining Timely Sowing of Wheat as an Adaptation to Climate Change in Eastern India

Abstract: Climate change is predicted to negatively impact wheat yields across northern India, primarily as a result of increased heat stress during grain filling at the end of the growing season. One way that farmers may adapt is by sowing their wheat earlier to avoid this terminal heat stress. However, many farmers in the eastern Indo-Gangetic Plains (IGP) sow their wheat later than is optimal, likely leading to yield reductions. There is limited documentation of why farmers sow their wheat late and the potential cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…There are several reasons our model may perform better through time in the west compared with the east. First, there is more variability in sowing patterns through time in the east; previous studies have shown that wheat planting date in the eastern IGP is sensitive to the timing of monsoon onset, and thus may fluctuate from year to year [24]. Second, it is possible that our accuracies are lower in the eastern IGP partly due to lower data quality.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are several reasons our model may perform better through time in the west compared with the east. First, there is more variability in sowing patterns through time in the east; previous studies have shown that wheat planting date in the eastern IGP is sensitive to the timing of monsoon onset, and thus may fluctuate from year to year [24]. Second, it is possible that our accuracies are lower in the eastern IGP partly due to lower data quality.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have also shown that it is possible for classification models to transfer well to other sites and time periods [23], increasing our ability to produce large-scale maps of zero tillage use across space and time. Yet, it is unclear how well classification models, such as random forest, may generalize in smallholder systems given the large heterogeneity in farm management, even across small spatial scales [24,25] and across multiple years [26].…”
Section: Introductionmentioning
confidence: 99%
“…Field management across this region is extremely heterogeneous, making it a complex system in which to map tillage practices using one universal algorithm. The sowing dates of wheat vary widely across the study region, ranging from mid-November to early January [ 35 ]. Wheat variety planted and input use, including fertilizer and irrigation, is also highly variable, with significant heterogeneity even across neighboring fields [ 19 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sowing dates of wheat vary widely across the study region, ranging from mid-November to early January [ 35 ]. Wheat variety planted and input use, including fertilizer and irrigation, is also highly variable, with significant heterogeneity even across neighboring fields [ 19 , 35 ]. Most farmers clear rice residues prior to sowing wheat, though some farmers leave partial residues in field.…”
Section: Methodsmentioning
confidence: 99%
“…Number of farmers who sowed wheat after 30th November 2351 100 Source: Authors' calculation using the LDS data Could it be that the farmers in Bihar and EUP do not realize the negative impact of late sowing of wheat on crop yields? In a survey of 256 farmers in the Arrah district of Bihar, Newport et al (2020) found that most farmers realize there are benefits to sowing earlier.…”
Section: Unavailability Of Seed 59mentioning
confidence: 99%